Distribution pattern of nitrate and fluoride in shallow domestic groundwater wells in northern parts of Kelantan, Malaysia - Kishan Raj Pillai, Mathialagan; Mohammad Muqtada Ali Khan; Hafzan Eva Mansor (2016)
The present study deals with the distribution of nitrate and fluoride ions concentration in shallow domestic supply of groundwater wells in parts of Kelantan, Malaysia. Groundwater consumption is essential in sustaining commercial and economic activities. Groundwater is widely regarded as one of the major sources of supply for domestic and agricultural practices. For the present investigation, twenty nine groundwater samples and three surface water samples were collected during year 2015-2016. Efforts have been made to demarcate potential origins of nitrate ion and fluoride ion in groundwater. The results were also compared with the World Health Organization (WHO) and Ministry of Health (MOH) guidelines. From the analysis, it can be inferred that the majority of groundwater samples assimilate low to moderate nitrate ion and fluoride ion concentration. Though, in one groundwater samples in location P4, the concentration of nitrate ion rises close to the permissible limit of WHO and MOH guideline. The major sources of nitrate ion in shallow domestic bores and wells are identified from zones which practice high fertilizer applications, improper sewages discharged and areas with poor management of livestock waste dumping. Increased nitrate concentrations in groundwater may indicate to several complications in a soil structures for instances, loss of fertility in the soil layers, consequently resulting in eutrophication when the groundwater discharges into surface water. Solutions for these problems include appropriate placement of groundwater wells in relation to septic tanks and piping as well as treatment of drinking water. Proper movements such as regulating contaminants or point sources with a suitable and cost-effective process such as de-nitrification method are capable in reestablishing the water quality in a particular area. Besides, strict regulation should also be brought to conserve the class of groundwater by penalizing the violators.